Atypical virulence of Leptospira kirschneri serogroup Icterohaemorrhagiae isolated from capybaras (Hydrochoerus hydrochaeris) in hamster model. (January 2019) - Barbosa, Cristina; Martins, Gabriel; Lilenbaum, Walter
Abstract: Leptospirosis is an important zoonotic disease and, in urban areas, rodents are considered the main reservoir of Leptospira to human hosts. It has been described that capybaras, the world largest rodent, also harbor and shed leptospires by urine. Although not virulent to their hosts, strains of rodent origin are virulent for the hamster. In this context we aim to investigate the virulence of Leptospira kirschneri strains of serogroup Icterohaemorrhagiae recovered from capybaras in Brazil in the hamster model. Five isolates of Leptospira recovered from asymptomatic capybaras were submitted to virulence tests following the suggested protocols and the 3Rs policy for experimental science. Briefly, 1 ml of 1 × 10 8 leptospires was inoculated intraperitoneally four times in one hamster for each strain. Four days after inoculation, a blood sample was collected via the gingival route for confirmation of blood culture infection. The infected animals were kept isolated in microisolators to observe clinical signs and monitored daily till day 21 post-inoculation. None strain caused acute disease in hamsters but were able to colonize their kidneys. The present study demonstrated that although Icterohaemorrhagiae strains are often reported as virulent, not all strains of that serogroup are indeed aggressive. Concluding, we report that strains of L. kirschneri serogroup Icterohaemorrhagiae recovered from healthy capybaras presented an atypical virulence to the hamster model, what reinforces that virulence is an intrinsic strains characteristic. Highlights: Not all strains of serogroup Icterohaemorrhagiae are indeed aggressive. L. kirschneri serogroup Icterohaemorrhagiae infects hamster but do not lead to death. Virulence of strains is not directly related to of the same serogroup.